Intrabiliary Migrated Clips and Coils as a Nidus for Biliary Stone Formation: A Rare Complication following Laparoscopic Cholecystectomy - Anne M. Schreuder; Thomas M. van Gulik; Erik A.J. Rauws (Case Reports in Gastroenterology, 2018)
Clips inserted during laparoscopic cholecystectomy (LC) may migrate into the biliary system and function as a nidus for the formation of gallstones. Here, we present a series of 4 patients who presented with this rare complication 5–17 years after LC. All 4 patients presented with symptomatic choledocholithiasis with biochemical and radiological signs of biliary obstruction. Three patients also had fever and infectious parameters, compatible with concurrent cholangitis. All patients successfully underwent endoscopic retrograde cholangiopancreatography (ERCP) with papillotomy and stone extraction. Patients with cholangitis also had antibiotic treatment. In 3 patients, obstruction of the common bile duct was caused by a single, relatively large stone that had formed around a clip (supposedly the cystic duct clip). In 1 patient, multiple stones had formed around an intrabiliary migrated cluster of coils that had been used for arterial embolization of a pseudo-aneurysm of the right hepatic artery. In conclusion, surgical clips and coils can migrate into the biliary tract and serve as a nidus for the formation of bile duct stones. Although rare, this complication should caution surgeons not to place clips “at random” during cholecystectomy. Patients with this rare complication are best managed by ERCP in combination with sphincterotomy and stone extraction.